Visualization of Sales Danalyser Data in Dashboard Form Google Data Studio - Agung Surya Maulana; Fauzi Erwis; yanto, Budi Yanto (Journal of ICT Applications System, 2023)
In the business sector, the use of information technology is used as a means of supporting company performance. Data visualization is the answer to simplifying complex data into a graphical format so that it is easier to understand the business. Managing sales data is an important process that must be carried out by companies. With good data management, companies get more value. This added value includes information supporting decision making, in order to increase the efficiency and effectiveness of company operations. This research uses data on sales of goods obtained from the internet, namely 69 data. The research was carried out with the help of Google Data Studio tools for creating dashboards. The results obtained are that there are several elements that help make it easier to read information, namely scorecard elements, Pie Chart elements, bar chart elements, geographic diagram elements, and table elements. The Scorecard element displays total income, average price of goods, total items sold, and total buyers. In the Pie Chart, the product insight is displayed in percent, the items that sell best are P010. The bar chart element displays total sales for each month, the highest sales were in August 2021. The geographic diagram element displays the distribution of sales to various countries. The table element displays insight information on price cuts or discounts.